ARTISTIC INTERPRETATION OF BABUR’S GREAT BABURNAMA AND LYRIC WORKS IN UZBEK LITERATURE (TAMADDUN NURI JURNALI, 2024)
The article provides a comprehensive overview of the life, accomplishments, and cultural impact of Zahiriddin Muhammad Babur, a prominent Central Asian figure known for his roles as a poet, king, and conqueror. Babur's early life, rise to power, and establishment of the Mughal Dynasty in India are detailed, highlighting his military prowess and diplomatic strategies. His literary contributions, including the renowned "Baburnama" and "Kabul Devonu," are explored, showcasing his poetic talent and scholarly pursuits. The article also discusses Babur's influence on literature and culture, with translations of his works into various languages and adaptations into novels by Western and Indian authors.